Rallying for immigrant rights the fight for inclusion in 21st century America - Voss, Kim; Bloemraad, Irene, 1972- (University of California Press, 2011)
"From Alaska to Florida, millions of immigrants and their supporters took to the streets across the United States to rally for immigrant rights in the spring of 2006. The scope and size of their protests, rallies, and boycotts made these the most significant events of political activism in the United States since the 1960s. This accessibly written volume offers the first comprehensive analysis of this historic moment. Perfect for students and general readers, its essays, written by a multidisciplinary group of scholars and grassroots organizers, trace the evolution and legacy of the 2006 protest movement in engaging, theoretically informed discussions. The contributors cover topics including unions, churches, the media, immigrant organizations, and immigrant politics"--